Body Composition Evaluation During The Competitive Season Of An NCAA Division II Men's Soccer Team - Lunn, William; Axtell, Robert (Medicine & Science in Sports & Exercise, 2025)
Keywords: Athletes; Body fat percentage; Competitive athletes; Composition (language); Division (mathematics); Fat mass; Lean body mass; Team sport; dept.hms

Muscular Strength Assessment - Axtell, Robert (ACSM's Exercise Testing and Prescription, 2023)
Keywords: dept.hms

Exercise Prescription - Older Adults - Axtell, Robert; Robertson, M. I. (ACSM's Exercise Testing and Prescription, 2023)
Keywords: dept.hms

Validity and reliability of the lode excalibur sport cycle ergometer for the wingate anaerobic test - Lunn, William R.; Axtell, Robert S. (The Journal of Strength & Conditioning Research, 2019)
Lunn, WR and Axtell, RS. Validity and reliability of the Lode Excalibur Sport cycle ergometer for the Wingate Anaerobic Test. J Strength Cond Res XX(X): 000–000, 2019—Although multiple testing devices advertise Wingate Anaerobic Test (WAnT), capability, reliability, and validity data are sparse. The purpose was to determine whether the Lode Excalibur Sport cycle ergometer is a reliable and valid instrument to conduct the 30-second WAnT when compared with the Monark 894e Peak Bike ergometer. Recreationally active men (n = 49; 20.6 ± 2.5 years; 1.75 ± 0.07 m; and 79.1 ± 9.8 kg) completed four 30-second WAnTs: 2 each on the Lode and the Monark ergometers for peak power (PP), mean power (MP), minimum power (MinP), fatigue index (FI), and peak cadence (vmax) measurement. Interday and interunit correlation, multivariate analysis of variance, regression, and Bland-Altman analysis determined reliability and validity. Cohen's d was used to determine effect size. Relative reliability (intraclass correlation coefficient) with 95% confidence interval for Monark and Lode was very high for PP, MP, MinP, and vmax and high for FI (r > 0.83; coefficient of variation ≤ 27.0%; p < 0.01). Interunit correlation was strong for PP, MP, MinP, and vmax (r > 0.75; p < 0.001) and moderate for FI (p = 0.001). Lode PP and FI values were significantly less (p < 0.001; d > 1.18) and MinP, MP, and vmax significantly greater (p ≤ 0.001; d > 0.51) than Monark. Proportional bias was demonstrated for all variables (p < 0.04; d > 2.68) except vmax. The Lode ergometer reliably provides WAnT outcomes and correlates well to the Monark ergometer. However, differences in power values and proportional bias between differently braked instruments prevent use of the Lode ergometer for comparison of WAnT data with normative data generated by the Monark ergometer.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lunnValidityReliabilityLode2019
Keywords: dept.hms; peer-reviewed

Muscle strength assessment - Axtell, Robert S. (ACSM's Exercise Testing and Prescription, 2018)
ACSM’S Exercise Testing and Prescription adapts and expands upon the assessment and exercise prescription-related content from ACSM’s Resource Manual for Guidelines for Exercise Testing and Prescription, 7th Edition, to create a true classroom resource. Fully aligned with the latest edition of ACSM’s flagship title, ACSM’s Guidelines for Exercise Testing and Prescription , this practical resource walks students through the process of selecting and administering fitness assessments, using Guidelines to interpret results, and drafting an exercise prescription that is in line with Guidelines parameters .Designed for today’s learners, the text is written in a clear, concise style, and enriched by visuals that promote student engagement. As an American College of Sports Medicine publication, the book offers the unsurpassed quality and excellence that has become synonymous with titles by the leading exercise science organization in the world.The nuances of fitness assessment and the particulars of crafting exercise prescriptions are explored in expansive sections throughout the book.A full section devoted to Special Populations prepares students to meet the needs of the full range of both typically healthy and special needs clients they’ll see in practice.Comprehensive case studies written by experts to reinforce practical applications of concepts.A wide range of online resources includes laboratory materials and activities that provide opportunities for hands-on learning, and a library of journal articles that helps students connect research to practice.100% alignment with the most up-to-date version of the ACSM’s Guidelines for Exercise Testing and Prescription enhances the learning experience, making it easy to go back and forth between Guidelines and the text.eBook available. Fast, smart, and convenient, today’s eBooks can transform learning. These interactive, fully searchable tools offer 24/7 access on multiple devices, the ability to highlight and share notes, and much more.
Keywords: dept.hms

Special considerations for the lifespan: Elderly population - Robertson, M.I.; Axtell, Robert (ACSM's Exercise Testing and Prescription, 2018)
ACSM’S Exercise Testing and Prescription adapts and expands upon the assessment and exercise prescription-related content from ACSM’s Resource Manual for Guidelines for Exercise Testing and Prescription, 7th Edition, to create a true classroom resource. Fully aligned with the latest edition of ACSM’s flagship title, ACSM’s Guidelines for Exercise Testing and Prescription , this practical resource walks students through the process of selecting and administering fitness assessments, using Guidelines to interpret results, and drafting an exercise prescription that is in line with Guidelines parameters .Designed for today’s learners, the text is written in a clear, concise style, and enriched by visuals that promote student engagement. As an American College of Sports Medicine publication, the book offers the unsurpassed quality and excellence that has become synonymous with titles by the leading exercise science organization in the world.The nuances of fitness assessment and the particulars of crafting exercise prescriptions are explored in expansive sections throughout the book.A full section devoted to Special Populations prepares students to meet the needs of the full range of both typically healthy and special needs clients they’ll see in practice.Comprehensive case studies written by experts to reinforce practical applications of concepts.A wide range of online resources includes laboratory materials and activities that provide opportunities for hands-on learning, and a library of journal articles that helps students connect research to practice.100% alignment with the most up-to-date version of the ACSM’s Guidelines for Exercise Testing and Prescription enhances the learning experience, making it easy to go back and forth between Guidelines and the text.eBook available. Fast, smart, and convenient, today’s eBooks can transform learning. These interactive, fully searchable tools offer 24/7 access on multiple devices, the ability to highlight and share notes, and much more.
Keywords: dept.hms

Effects of sprint interval training and body weight reduction on power to weight ratio in experienced cyclists. - Lunn, William R; Finn, Joan A; Axtell, Robert S (Journal of strength and conditioning research, 2009)
The purpose of this study was to determine the effect of supramaximal sprint interval training (SIT), body weight reduction, and a combination of both treatments on peak and average anaerobic power to weight ratio (PPOan:Wt, APOan:Wt) by manipulating peak and average anaerobic power output (PPOan, APOan) and body weight (BW) in experienced cyclists. Participants (N = 34, age = 38.0 +/- 7.1 years) were assigned to 4 groups for a 10-week study. One group performed twice-weekly SIT sessions on a cycle ergometer while maintaining body weight (SIT). A second group did not perform SIT but intentionally reduced body weight (WR). A third group simultaneously performed SIT sessions and reduced body weight (SIT+WR). A control group cycled in their normal routine and maintained body weight (CON). The 30-second Wingate Test assessed pretest and posttest POan:Wt scores. There was a significant mean increase (p < 0.05) from pretest to posttest in PPOan:Wt and APOan:Wt (W x kg(-1)) scores in both SIT (10.82 +/- 1.71 to 11.92 +/- 1.77 and 8.05 +/- 0.64 to 8.77 +/- 0.64, respectively) and WR (10.33 +/- 2.91 to 11.29 +/- 2.80 and 7.04 +/- 1.45 to 7.62 +/- 1.24, respectively). PPOan and APOan (W) increased significantly only in SIT (753.7 +/- 121.0 to 834.3 +/- 150.1 and 561.3 +/- 62.5 to 612.7 +/- 69.0, respectively). Body weight (kg) decreased significantly in WR and SIT + WR (80.3 +/- 13.7 to 75.3 +/- 11.9 and 78.9 +/- 10.8 to 73.4 +/- 10.8, respectively). The results demonstrate that cyclists can use SIT sessions and body weight reduction as singular training interventions to effect significant increases in anaerobic power to weight ratio, which has been correlated to enhanced aerobic cycling performance. However, the treatments were not effective as combined interventions, as there was no significant change in either PPOan:Wt or APOan:Wt in SIT + WR.
7 citations (Crossref) [2023-10-31] Place: United States Lunn, William R. Exercise Science Department, Southern Connecticut State University, New Haven, Connecticut 06515, USA. wlunn25@comcast.net
Keywords: *Bicycling/ph [Physiology]; *Physical Education and Training/mt [Methods]; *Weight Loss; Adult; Analysis of Variance; Bicycling; Body Composition; Body Mass Index; Body Weight; Female; Humans; Male; Physical Education and Training; Physical Endurance; Physical Endurance/ph [Physiology]; Reproducibility of Results; Weight Loss; Wingate test; adult; analysis of variance; article; bicycle; body composition; body mass; body weight; dept.hms; endurance; female; human; male; methodology; peer-reviewed; physical education; physiology; reproducibility; weight reduction

Potential impact of a 500-mL water bolus and body mass on plasma osmolality dilution - Sollanek, Kurt J.; Kenefick, Robert W.; Cheuvront, Samuel N.; Axtell, Robert S. (European Journal of Applied Physiology, 2011)
A methodological discrepancy exists in the hydration assessment literature regarding the establishment of euhydration, as some investigations utilize a prehydration technique, while others do not (overnight fluid/food fast). However, the degree that plasma osmolality (Posm) dilutes when using the pre-hydration method and how body mass/composition might influence the results is not known. Thirty subjects (22 M, 8 F; 20 ± 2 years (mean ± SD); 1.8 ± 0.1 m; 75.8 ± 13.5 kg) had P osm measured after an 8-h food and fluid fast (overnight fast) and 90 min after a 500-mL (4-9 mL/kg) water bolus (prehydration). From pre- to post-bolus, participants' P osm declined from 297 ± 3.5 to 295 ± 3.8 mmol/kg (p<0.05; Δ -1.7 ± 3.5 mmol/kg). One-third of the sample diluted to more than -3 mmol/kg. The effect of body mass on P osm dilution was investigated by comparing dilution in the ten lightest (62.8 ± 3.4 kg) and heaviest (92.0 ± 9.8 kg) participants; however, the change between the light (Δ -1.9 ± 3.8 mmol/kg) versus heavy groups (Δ -1.1 ± 3.0 mmol/kg) was not different (p>0.05). The correlation between body mass or total body water and change in P osm was weak (p>0.05), as was the correlation between relative fluid intake based on mass and change in P osm (p>0.05). The two methodologies appear to produce similar P osm values when measured in most individuals. However, the potential for significant dilution (>3 mmol/kg) should be considered when choosing the pre-hydration methodology. © Springer-Verlag (outside the USA) 2011.
17 citations (Crossref) [2023-10-31] Citation Key Alias: pop00120 tex.type: [object Object]
Keywords: Adolescent; Adult; Blood; Blood Chemical Analysis; Body Weight; Dehydration; Drinking; Female; Fluid intake; Humans; Hydration assessment; Hypohydration; Male; Osmolar Concentration; SCSU-student; Total body water; Water; Water-Electrolyte Balance; Young Adult; adolescent; adult; article; blood; blood analysis; body weight; clinical trial; dehydration; dept.hms; drinking; drug effect; electrolyte balance; female; human; male; metabolism; osmolarity; physiology; water

Changes in Lower Body Muscular Performance Following a Season of NCAA Division I Men’s Lacrosse - Talpey, Scott W.; Axtell, Robert; Gardner, Elizabeth; James, Lachlan (Sports, 2019)
The tactical and technical components of training become a primary emphasis, leaving less time for targeted development of physical qualities that underpin performance during the competition phase of a training program. A deemphasis on physical preparation during the in-season training phase may make athletes more susceptible to injury and decrease performance on the field. Two weeks prior to the start and one week following the conclusion of the 16-week collegiate lacrosse season, lower body force production was assessed in eight National Collegiate Athletic Association (NCAA) Division I Men’s Lacrosse athletes. Lower body force production capabilities were determined via the performance of countermovement jumps (CMJ) and drop jumps (DJ) performed on a force plate and isokinetic strength testing of the quadriceps and hamstring muscle groups across three velocities. Isokinetic strength of the hamstrings and the hamstring to quadriceps strength ratio were maintained or increased over the course of the competition phase of training. Relative peak force obtained from the CMJ and the reactive strength index from the DJ decreased significantly over the season. The maintenance of isokinetic strength and the decrease in CMJ and DJ performance may indicate the presence of neuromuscular fatigue that accumulated over the course of the season.
5 citations (Crossref) [2023-10-31] Number: 1
Keywords: Isokinetic; Power; Reactive strength; Strength; dept.hms; isokinetic; peer-reviewed; power; reactive strength; strength

Impaired autonomic function in normotensive obese children - Latchman, Peter L; Mathur, Madhu; Bartels, Matthew N; Axtell, Robert S; Meersman, Ronald E De (Clinical Autonomic Research, 2011)
Purpose To evaluate baroreflex sensitivity and autonomic control in a cohort of normotensive obese (OB) children. Method A cross-sectional investigation, in which, baroreflex sensitivity and autonomic control were evaluated using transfer function and power spectral density analysis (PSDA) of the electrocardiogram and beat-to-beat blood pressures in normotensive OB children and normal weight normotensive controls. All methods used were noninvasive and data were captured while seated and at rest. Results The OB and control subjects non-obese (NO) were of similar age (OB 9.1 ± 1.9 years vs.NO9.2 ± 1.4 years). The OB group was classified as having a BMI greater than the 95th percentile adjusted for age and gender, and a NO group with a BMI at or less than the 95th percentile (BMI percentile OB. 97.5 ± 1.3 vs. NO 58.5 ± 24.1). Both groups had similar normotensive blood pressures. T tests revealed that baroreflex sensitivity and HFRR were significantly reduced in the OB 9.2 ± 2.7 vs. 15.2 ± 4.7 (ms/mmHg) and 6.7 ± 1.1 vs. 8.2 ± 1.1 ms 2, respectively, while LF SBP and LF/HF ratio were significantly increased in the OB 11.9 ± 5.6 vs. 8.2 ± 4.7 mmHg 2 and 1.2 ± 0.7 vs. 0.54 ± 0.3, respectively. Conclusions Normotensive OB children exhibited significantly reduced baroreflex sensitivity, parasympathetic control as well as increased sympathetic control when compared with healthy, NO controls. Findings in this investigation raise the awareness that autonomic dysfunction is present in young OB normotensive children. © Springer-Verlag 2011.
29 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/000-898-861-083-084 tex.type: [object Object]
Keywords: Autonomic Nervous System; Autonomic modulation; Baroreflex sensitivity; Blood Pressure; Child; Cross-Sectional Studies; Female; Humans; Male; Normotensive; Obese children; Obesity; article; autonomic dysfunction; blood pressure; blood pressure measurement; body mass; body weight; child; clinical article; controlled study; dept.hms; electrocardiogram; female; human; male; obesity; pressoreceptor reflex; school child; sensitivity analysis

Cannabidiol supplementation alleviates anxiety, mitigates pain, extends endurance, and facilitates greater exercise exertion: 277 - Lunn, William R.; Axtell, Robert S. III; Venard, Anna; Bodurtha, Phillip; Brunello, Greta; Bukowski, Zachary (Medicine & Science in Sports & Exercise, 2023)
An abstract is unavailable.
Keywords: dept.hms; peer-reviewed

Spontaneous baroreflex sensitivity in young normotensive African-American women - Latchman, Peter; Gates, Gregory J; Axtell, Robert S; Pereira, Jason; Bartels, Matthew N; Meersman, Ronald Edmond De (Clinical Autonomic Research, 2013)
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/109-712-863-816-776 tex.type: [object Object]
Keywords: African American; European American; adult; article; body mass; breathing rate; clinical article; controlled study; dept.hms; diastolic blood pressure; family history; female; human; hypertension; physical activity; pressoreceptor reflex; race difference; systolic blood pressure

Discriminative ability of lower limb strength and power measures in lacrosse athletes - Talpey, Scott W.; Axtell, Robert; Gardner, Elizabeth; Maloney, Maggie; Newman, Thomas; Cordone, Jason; O’Grady, Mathew (International Journal of Sports Medicine, 2023)
The objective of this investigation was to compare isokinetic strength, countermovement jump and drop jump variables between high-contributors and low-contributors within NCAA Division I Men’s and Women’s lacrosse athletes. Men’s (N=36) and Women’s (N=30) NCAA Division I lacrosse athletes completed strength testing of the quadriceps and hamstring across three speeds (60°·s−1, 180°·s−1, 300°·s−1), countermovement and drop jumps. To determine the discriminative ability of select lower-limb strength and power characteristics participants were categorized as high-contributors (Males N=18, age=20.3±0.4 yrs, height=183.9±5.5 cm, mass=90.8±5.8 kg; Females N=15, age=20.8±0.8 yrs, height=169.3±6.7 cm, mass=64.1±7.2 kg) or low-contributors (Males N=18, age=19.5±0.2 yrs, height=184.1±5.6 cm; mass=87.9±8.1 kg; Females N=15, age=19.7±0.2 yrs, height=169.8±7.0 cm, mass=62.9±7.7 kg ) based upon the number of games the participants competed in during the regular season. Within the male cohort, moderate significant (p−1 (d=0.69) and peak power in countermovement jump (d=0.68). Within the women’s cohort a large (d=0.87) significant difference (p−1. Hamstring strength and lower-limb power are important strength measures for lacrosse performance and should be prioritized in training prescription for lacrosse athletes.
0 citations (Crossref) [2023-10-31]
Keywords: Key words countermovement jump; dept.hms; drop jump; female athlete; peer-reviewed; performance

Sex Differences in Response to a 12-Week Resistance Training Exercise Intervention After Cardiac Surgery: A Proof-of-Concept Intervention Trial - Safdar, Basmah; Jarman, Angela; Madsen, Tracy; DeLamielleure, Lauren; Zhou, Bin; Axtell, Robert; Geirsson, Arnar; Mangi, Abeel (Clinical Therapeutics, 2025)
Keywords: Cardiac rehabilitation (CR); Cardiac surgery; Cardiovascular disease (CVD); Intervention (counseling); Medicine; Nursing; Physical therapy; Randomized controlled trial; Resistance strength training; Resistance training; Safety and feasibility; Sex differences; Surgery; dept.hms; peer-reviewed

Effects of a Long-Term Physical Activity Program on Activity Patterns in Older Adults. - Wanigatunga, Amal A; Tudor-Locke, Catrine; Axtell, Robert S; Glynn, Nancy W; King, Abby C; McDermott, Mary M; Fielding, Roger A; Lu, Xiaomin; Pahor, Marco; Manini, Todd M (Medicine and science in sports and exercise, 2017)
PURPOSE: To examine the effect of a long-term structured physical activity (PA) intervention on accelerometer-derived metrics of activity pattern changes in mobility-impaired older adults., METHODS: Participants were randomized to either a PA or health education (HE) program. The PA intervention included a walking regimen with strength, flexibility, and balance training. The HE program featured health-related discussions and a brief upper body stretching routine. Participants (n = 1341) wore a hip-worn accelerometer for >=10 h.d for >=3 d at baseline and again at 6, 12, and 24 months postrandomization. Total PA (TPA)-defined as movements registering 100+ counts per minute-was segmented into the following intensities: low-light PA (LLPA; 100-759 counts per minute), high light PA (HLPA; 760-1040 counts per minute), low moderate PA (LMPA; 1041-2019 counts per minute), and high moderate and greater PA (HMPA; 2020+ counts per minute). Patterns of activity were characterized as bouts (defined as the consecutive minutes within an intensity)., RESULTS: Across groups, TPA decreased an average of 74 min.wk annually. The PA intervention attenuated this effect (PA = -68 vs HE: -112 min.wk, P = 0.002). This attenuation shifted TPA composition by increasing time in LLPA (10+ bouts increased 6 min.wk), HLPA (1+, 2+, 5+, and 10+ bouts increased 6, 3, 2, and 1 min.wk, respectively), LMPA (1+, 2+, 5+, and 10+ bouts increased: 19, 17,16, and 8 min.wk, respectively), and HMPA (1+, 2+, 5+, and 10+ bouts increased 23, 21, 17, and 14 min.wk, respectively)., CONCLUSIONS: The PA intervention increased PA by shifting the composition of activity toward higher-intensity activity in longer-duration bouts. However, a long-term structured PA intervention did not completely eliminate overall declines in total daily activity experienced by mobility-impaired older adults.
26 citations (Crossref) [2023-10-31] Place: United States Wanigatunga, Amal A. 1Department of Epidemiology, Johns Hopkins University, Baltimore, MD; 2Department of Kinesiology, University of Massachusetts Amherst, Amherst, MA; 3Exercise Science Department, Southern Connecticut State University, New Haven, CT; 4Department of Epidemiology, University of Pittsburgh, Pittsburgh, PA; 5Department of Health Research and Policy and Department of Medicine, Stanford University, School of Medicine, Stanford, CA; 6Feinberg School of Medicine, Northwestern University, Evanston, IL; 7Nutrition, Exercise Physiology and Sarcopenia Laboratory, Jean Mayer United States Department of Agriculture Human Nutrition Research Center on Aging, Tufts University, Boston, MA; 8Department of Biostatistics, University of Florida, Gainesville, FL; and 9Department of Aging and Geriatric Research, University of Florida, Gainesville, FL.
Keywords: *Aged/ph [Physiology]; *Exercise; *Health Promotion; ACCELEROMETER; ACTIVITY BOUTS; Accelerometry; Age Factors; Aged; Aged; 80 and over; ELDERLY; Exercise; Female; Health Promotion; Humans; LIGHT-INTENSITY PHYSICAL ACTIVITY; Male; Mobility Limitation; PHYSICAL ACTIVITY INTERVENTION; Program Evaluation; Sedentary Behavior; Sedentary Lifestyle; accelerometry; age; aged; clinical trial; controlled study; dept.hms; exercise; female; health promotion; human; male; multicenter study; peer-reviewed; physiology; program evaluation; randomized controlled trial; sedentary lifestyle; very elderly; walking difficulty

College community–based physical activity support at a public university during the COVID-19 pandemic: retrospective longitudinal analysis of intra- versus interpersonal components for uptake and outcome association - Ash, Garrett; Mak, Selene; Haughton, Adrian; Augustine, Madilyn; Bodurtha, Phillip; Axtell, Robert; Borsari, Beatrice; Liu, Jason; Lou, Shaoke; Xin, Xin; Fucito, Lisa; Jeon, Sangchoon; et al. (JMIR mhealth and uhealth, 2025)
Background College students are vulnerable to setting long-term trajectories of low physical activity (PA) but are reachable via mobile health fitness tracking (eg, mobile health step counting) and interpersonal support tailored to the college community. However, no studies have statistically isolated the appeal and influence of these intra- and interpersonal components in college-based PA interventions. Objective This study retrospectively examined a college-based PA promotion program at a northeast US public university during the COVID-19 pandemic to (1) test the impact of student status on the use of intervention components and (2) determine whether such use was associated with successful retention and goal achievement in the program. Methods The university used a commercial platform for a 30-day PA promotion program during April 2021 with intrapersonal (step-tracker syncing, education, self-monitoring, and motivational messaging) and interpersonal (friend interactions and team games) components. App use was operationalized as intrapersonal (frequency of opening app, education, and self-monitoring) and interpersonal (friends made in-app and team affiliation and size). Results Campus-wide emails elicited sign-up by 156 undergraduate students, 57 graduate students, and 126 faculty and staff members. Objective 1 yielded the following results: undergraduates used the app less frequently (median 0.8, IQR 0.4-1.7 times per day) than other groups (graduate students: median 1.4, IQR 0.7-2.7 times per day; P=.01; faculty: median 1.3, IQR 0.7-2.7 times per day, H2=14.5; P=.001) but made the same number of friends (median 1-2) and teammates (median 8-9; P=.77 for friends and P=.93 for teammates). Objective 2 yielded the following results: most participants (313/335, 93.4%; 95% CI 90%-96%) were retained for the first 7 days, but by 30 days, retention dropped, most notably for undergraduate students (82/154, 53.2%; 95% CI 45%-61%), followed by graduate students (39/56, 70%; 95% CI 56%-81%) and faculty and staff (93/125, 74.4%; 95% CI 66%-82%; χ22=12.6; P<.001). Retention was associated with app engagement frequency (model hazard ratio 0.56, 95% CI 0.43-0.72; P<.001) and affiliation with a team having high median app engagement and a large size (intracluster correlation coefficient 0.064, 95% CI 0.001-0.164, P=.05). Meeting a daily step goal was associated with app engagement frequency (β=.72, SE=0.21; P=.001), number of friends (β=.40, SE 0.20; P=.04), and an initial motive of maintaining or increasing (rather than starting) PA (β=.99, SE=0.21; P<.001). Conclusions College students, compared with faculty and staff, used the app less frequently, used the app for a shorter duration before abandonment, and met the step goal on fewer days. Engagement with the program was associated with longer retention and better PA outcomes, which were critically modified by the interpersonal engagement. These findings suggest that college students using virtual PA support during times of physical isolation could benefit from more tailored implementation strategies (eg, timed prompts and team reassignments).
Keywords: Computer science; Coronavirus disease 2019 (COVID-19); Demography; Disease; Gerontology; Infectious disease (medical specialty); Internal medicine; Medicine; Preprint; Sociology; dept.hms

Dose of physical activity, physical functioning and disability risk in mobility-limited older adults: Results from the LIFE study randomized trial. - Fielding, Roger A; Guralnik, Jack M; King, Abby C; Pahor, Marco; McDermott, Mary M; Tudor-Locke, Catrine; Manini, Todd M; Glynn, Nancy W; Marsh, Anthony P; Axtell, Robert S; Hsu, Fang-Chi; Rejeski, W Jack; et al. (PLoS ONE, 2017)
Understanding the minimal dose of physical activity required to achieve improvement in physical functioning and reductions in disability risk is necessary to inform public health recommendations. To examine the effect of physical activity dose on changes in physical functioning and the onset of major mobility disability in The Lifestyle Interventions and Independence for Elders (LIFE) Study. We conducted a multicenter single masked randomized controlled trial that enrolled participants in 2010 and 2011 and followed them for an average of 2.6 years. 1,635 sedentary men and women aged 70-89 years who had functional limitations were randomized to a structured moderate intensity walking, resistance, and flexibility physical activity program or a health education program. Physical activity dose was assessed by 7-day accelerometry and self-report at baseline and 24 months. Outcomes included the 400 m walk gait speed, the Short Physical Performance Battery (SPPB), assessed at baseline, 6, 12, and 24 months, and onset of major mobility disability (objectively defined by loss of ability to walk 400 m in 15 min). When the physical activity arm or the entire sample were stratified by change in physical activity from baseline to 24 months, there was a dose-dependent increase in the change in gait speed and SPPB from baseline at 6, 12, and 24 months. In addition, the magnitude of change in physical activity over 24 months was related to the reduction in the onset of major mobility disability (overall P < 0.001) (highest versus the lowest quartile of physical activity change HR 0.23 ((95% CI:0.10-0.52) P = 0.001) in the physical activity arm. We observed a dose-dependent effect of objectively monitored physical activity on physical functioning and onset of major mobility disability. Relatively small increases (> 48 minutes per week) in regular physical activity participation had significant and clinically meaningful effects on these outcomes., TRIAL REGISTRATION: ClinicalsTrials.gov NCT00116194.
89 citations (Crossref) [2023-10-31] Place: United States Fielding, Roger A. Nutrition, Exercise Physiology, and Sarcopenia Laboratory, Jean Mayer USDA Human Nutrition Research Center on Aging at Tufts University, Boston, MA, United States of America. Guralnik, Jack M. Department of Epidemiology and Public Health, University of Maryland School of Medicine, 4655 W. Baltimore Street, Baltimore, MD, United States of America. King, Abby C. Department of Health Research & Policy, and Stanford Prevention Research Center, Department of Medicine, Stanford University Medical School, Stanford, CA, United States of America. Pahor, Marco. Department of Aging and Geriatric Research, University of Florida College of Medicine, Gainesville, FL, United States of America. McDermott, Mary M. Department of Medicine, Northwestern University Feinberg School of Medicine, 750 N Lake Shore Drive, 10th Floor, Chicago, IL, United States of America. Tudor-Locke, Catrine. Department of Kinesiology, University of Massachusetts Amherst, Amherst, MA, United States of America. Tudor-Locke, Catrine. Pennington Biomedical Research Center, Louisiana State University System, Baton Rouge, LA, United States of America. Manini, Todd M. Department of Aging and Geriatric Research, University of Florida College of Medicine, Gainesville, FL, United States of America. Glynn, Nancy W. Center for Aging and Population Health, Department of Epidemiology, Graduate School of Public Health, University of Pittsburgh, Pittsburgh, PA, United States of America. Marsh, Anthony P. Department of Health and Exercise Science, Wake Forest University, Winston-Salem, NC, United States of America. Axtell, Robert S. Department of Exercise Science, Southern Connecticut State University, New Haven, CT. Hsu, Fang-Chi. Department of Biostatistical Sciences, Division of Public Health Sciences, Wake Forest School of Medicine, Winston-Salem, NC, United States of America. Rejeski, W Jack. Center for Aging and Population Health, Department of Epidemiology, Graduate School of Public Health, University of Pittsburgh, Pittsburgh, PA, United States of America.
Keywords: *Activities of Daily Living; *Disabled Persons; *Exercise; *Mobility Limitation; Activities of Daily Living; Aged; Aged; 80 and over; Article; Disabled Persons; Exercise; Female; Humans; Male; Mobility Limitation; accelerometry; aged; controlled study; daily life activity; dept.hms; disabled person; education program; exercise; exercise intensity; female; human; incidence; major clinical study; male; multicenter study; outcome assessment; peer-reviewed; physical activity; physical activity; capacity and performance; physical disability; physical functioning; physical mobility; physical performance; randomized controlled trial; resistance training; risk assessment; risk factor; sedentary lifestyle; self report; very elderly; walking difficulty; walking speed

Evaluating accelerometry thresholds for detecting changes in levels of moderate physical activity and resulting major mobility disability - Rejeski, W. Jack; Walkup, Michael P.; Fielding, Roger A.; King, Abby C.; Manini, Todd M.; Marsh, Anthony P.; McDermott, Mary McGrae; Miller, Emily Y; Newman, Anne B.; Tudor-Locke, Catrine; Axtell, Robert S.; Miller, Michael E. (Journals of Gerontology Series A-biological Sciences and Medical Sciences, 2018)
Background: An important decision with accelerometry is the threshold in counts per minute (CPM) used to define moderate to vigorous physical activity (MVPA). We explore the ability of different thresholds to track changes in MVPA due to a physical activity (PA) intervention among older adults with compromised function: 760 CPM, 1,041 CPM, and an individualized threshold. We also evaluate the ability of change in accelerometry and self-reported PA to attenuate treatment effects on major mobility disability (MMD). Methods: Data from a week of hip worn accelerometers and self-reported PA data (30-day recall) were examined from baseline, 6-, 12-, and 24-months of follow-up on 1,528 older adults. Participants were randomized to either PA or Health Education (HE). MMD was objectively defined by loss of ability to walk 400 m during the follow-up. Results: The three thresholds yielded similar and higher levels of MVPA for PA than HE (p ¡ .001), however, this difference was significantly attenuated in participants with lower levels of physical function. Self-reported PA that captured both walking and strength training totally attenuated the intervention effect for MMD, an 18% reduction to a 3% increase. Accelerometer CPMs showed less attenuation of the intervention effect. Conclusions: Accelerometry assessment within the LIFE study was not sensitive to change in level in physical activity for older adults with very low levels of physical function. A combination of self-report and objective measures are recommended for use in physical activity intervention studies of the elderly; limitations of accelerometry deserve closer attention.
6 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000430696300014 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Accelerometry; Aged; Aged; 80 and over; Female; Geriatric Assessment; Humans; LIFE-study; Male; Mobility Disability; Mobility Limitation; Motor Activity; Older Adults; Thresholds; Walking; accelerometry; aged; clinical trial; controlled study; dept.hms; female; geriatric assessment; human; male; motor activity; multicenter study; peer-reviewed; physiology; procedures; randomized controlled trial; very elderly; walking; walking difficulty

Device-measured physical activity as a predictor of disability in mobility-limited older adults - Mankowski, Robert T.; Anton, Stephen D.; Axtell, Robert; Chen, Shyh-Huei; Fielding, Roger A.; Glynn, Nancy W.; Hsu, Fang-Chi; King, Abby C.; Layne, Andrew S.; Leeuwenburgh, Christiaan; Manini, Todd M.; Marsh, Anthony P.; et al. (Journal of the American Geriatrics Society, 2017)
OBJECTIVES: To examine associations between objectively measured physical activity (PA) and incidence of major mobility disability (MMD) and persistent MMD (PMMD) in older adults in the Lifestyle Interventions and Independence for Elders (LIFE) Study. DESIGN: Prospective cohort of individuals aged 65 and older undergoing structured PA intervention or health education. SETTING: The LIFE Study was a multicenter (eight sites) randomized controlled trial designed to compare the efficacy of a long-term structured PA intervention with that of a health education (HE) program in reducing the incidence of MMD in mobility-limited older adults. PARTICIPANTS: LIFE Study participants (n = 1,590) had a mean age +/- standard deviation of 78.9 +/- 5.2, low levels of PA, and measured mobility-relevant functional impairment at baseline. MEASUREMENTS: Activity data were collected using hip-worn 7-day accelerometers at baseline and 6, 12, and 24 months after randomization to test for associations with incident MMD and PMMD (¿= 2 consecutive instances of MMD). RESULTS: At baseline, every 30 minutes spent being sedentary (¡100 accelerometry counts per minute) was associated with higher rate of subsequent MMD (10%) and PMMD (11%) events. Every 500 steps taken was associated with lower rate of MMD (15%) and PMMD (18%). Similar associations were observed when fitting accelerometry-based PA as a time-dependent variable. CONCLUSION: Accelerometry-based PA levels were strongly associated with MMD and PMMD events in older adults with limited mobility. These results support the importance of daily PA and lower amounts of sedentary time levels in this population and suggest that accelerometry may be a useful tool for assessing risk of mobility disability.
25 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000417650000023, lens.org/040-976-851-672-995 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Accelerometry; Aged; Aged; 80 and over; Article; Disability Evaluation; Exercise; Female; Geriatric Assessment; Humans; Male; Mini Mental State Examination; Mobility Limitation; Physical Therapy Modalities; Pittsburgh Sleep Quality Index; Sedentary Lifestyle; Time Factors; accelerometry; aged; clinical trial; cohort analysis; controlled study; depression; dept.hms; disability; educational status; ethnic group; exercise; female; functional disease; geriatric assessment; health education; human; major clinical study; major mobility disability; male; marriage; mobility disability; multicenter study; older adults; peer-reviewed; persistent major mobility disability; physical activity; physiotherapy; procedures; prospective study; randomized controlled trial; sedentary lifestyle; sedentary time; sleep quality; time factor; very elderly; walking difficulty

Promoting physical activity for elders with compromised function: the Lifestyle Interventions and Independence for Elders (LIFE) Study physical activity intervention - Rejeski, W. Jack; Axtell, Robert; Fielding, Roger; Katula, Jeffrey; King, Abby C.; Manini, Todd M.; Marsh, Anthony P.; Pahor, Marco; Rego, Alvito; Tudor-Locke, Catrine; Newman, Mark; Walkup, Michael P.; et al. (Clinical Interventions in Aging, 2013)
The Lifestyle Interventions and Independence for Elders (LIFE) Study is a Phase III randomized controlled clinical trial (Clinicaltrials.gov identifier: NCT01072500) that will provide definitive evidence regarding the effect of physical activity (PA) on major mobility disability in older adults (70-89 years old) who have compromised physical function. This paper describes the methods employed in the delivery of the LIFE Study PA intervention, providing insight into how we promoted adherence and monitored the fidelity of treatment. Data are presented on participants' motives and self-perceptions at the onset of the trial along with accelerometry data on patterns of PA during exercise training. Prior to the onset of training, 31.4% of participants noted slight conflict with being able to meet the demands of the program and 6.4% indicated that the degree of conflict would be moderate. Accelerometry data collected during PA training revealed that the average intensity - 1,555 counts/minute for men and 1,237 counts/minute for women - was well below the cutoff point used to classify exercise as being of moderate intensity or higher for adults. Also, a sizable subgroup required one or more rest stops. These data illustrate that it is not feasible to have a single exercise prescription for older adults with compromised function. Moreover, the concept of what constitutes “moderate” exercise or an appropriate volume of work is dictated by the physical capacities of each individual and the level of comfort/stability in actually executing a specific prescription.
36 citations (Crossref) [2023-10-31] tex.orcid-numbers: Buford, Thomas W/0000-0002-9541-4358 Handberg, Eileen/0000-0002-7805-9577 Newman, Mark/0000-0002-0444-8246 tex.researcherid-numbers: Buford, Thomas W/B-1111-2011 Katula, Jeffrey/K-5905-2013 tex.unique-id: ISI:000324170300001
Keywords: Accelerometry; Aged; Aged; 80 and over; Aging; Compromised physical function; Exercise; Female; Health Promotion; Humans; Independent Living; Male; Mobility Limitation; Older adults; Physical disability; Qualitative Research; Risk Reduction Behavior; Sex Distribution; accelerometry; aged; aging; article; autoregulation; body mass; compromised physical function; computer interface; computer program; conceptual framework; controlled study; dept.hms; education; elderly care; ethnicity; exercise intensity; female; health education; human; human experiment; lifestyle; male; motor performance; normal human; older adults; phase 3 clinical trial; physical activity; physical capacity; physical disability; quality of life; randomized controlled trial; semi structured interview; sex difference; social behavior; social environment

A case for promoting movement medicine: preventing disability in the LIFE randomized controlled trial - Fanning, Jason; Rejeski, W Jack; Chen, Shyhhuei; Nicklas, Barbara J; Walkup, Michael P; Axtell, Robert S; Fielding, Roger A; Glynn, Nancy W; King, Abby C; Manini, Todd M; Mcdermott, Mary Mcgrae; Newman, Anne B; et al. (Journals of Gerontology Series A-biological Sciences and Medical Sciences, 2019)
Background: The movement profile of older adults with compromised function is unknown, as is the relationship between these profiles and the development of major mobility disability (MMD)-a critical clinical outcome. We first describe the dimensions of movement in older adults with compromised function and then examine whether these dimensions predict the onset of MMD. Methods: Older adults at risk for MMD (N = 1,022, mean age = 78.7 years) were randomized to receive a structured physical activity intervention or health education control. We assessed MMD in 6-month intervals (average follow-up of 2.2 years until incident MMD), with activity assessed at baseline, 6-, 12- and 24-month follow-up via accelerometry. Results: A principal components analysis of 11 accelerometer-derived metrics yielded three components representing lifestyle movement (LM), extended bouts of moderate-to-vigorous physical activity (MVPA), and stationary body posture. LM accounted for the greatest proportion of variance in movement (53%). Within health education, both baseline LM (HR = 0.74; 95% CI 0.62 to 0.88) and moderate-to-vigorous physical activity (HR = 0.69; 95% CI 0.54 to 0.87) were associated with MMD, whereas only LM was associated with MMD within physical activity (HR = 0.74; 95% CI 0.61 to 0.89). There were similar nonlinear relationships present for LM in both physical activity and health education (p ¡ .04), whereby risk for MMD was lower among individuals with higher levels of LM. Conclusions: Both LM and moderate-to-vigorous physical activity should be central in treatment regimens for older adults at risk for MMD.
8 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000491242600017, lens.org/077-007-606-131-474 tex.type: [object Object]
Keywords: Acceleration; Accelerometry; Age Factors; Aged; Aged; 80 and over; Aging; Confidence Intervals; Disability; Disability Evaluation; Exercise; Female; Geriatric Assessment; Humans; Linear Models; Male; Mobility Limitation; Physical Fitness; Physical activity; Prognosis; Sedentary; Sex Factors; Single-Blind Method; Walking Speed; acceleration; age; aged; aging; clinical trial; confidence interval; controlled study; dept.hms; disability; female; fitness; geriatric assessment; human; male; multicenter study; peer-reviewed; physiology; procedures; prognosis; randomized controlled trial; sex factor; single blind procedure; statistical model; very elderly; walking difficulty; walking speed

Actigraphy features for predicting mobility disability in older adults - Kheirkhahan, Matin; Tudor-Locke, Catrine; Axtell, Robert; Buman, Matthew P.; Fielding, Roger A.; Glynn, Nancy W.; Guralnik, Jack M.; King, Abby C.; White, Daniel K.; Miller, Michael E.; Siddique, Juned; Brubaker, Peter; et al. (Physiological Measurement, 2016)
Actigraphy has attracted much attention for assessing physical activity in the past decade. Many algorithms have been developed to automate the analysis process, but none has targeted a general model to discover related features for detecting or predicting mobility function, or more specifically, mobility impairment and major mobility disability (MMD). Men (N = 357) and women (N = 778) aged 70-89 years wore a tri-axial accelerometer (Actigraph GT3X) on the right hip during free-living conditions for 8.4 +/- 3.0 d. One-second epoch data were summarized into 67 features. Several machine learning techniques were used to select features from the free-living condition to predict mobility impairment, defined as 400 m walking speed ¡0.80 m s(-1). Selected features were also included in a model to predict the first occurrence of MMD-defined as the loss in the ability to walk 400 m. Each method yielded a similar estimate of 400 m walking speed with a root mean square error of similar to 0.07 m s(-1) and an R-squared values ranging from 0.37-0.41. Sensitivity and specificity of identifying slow walkers was approximately 70% and 80% for all methods, respectively. The top five features, which were related to movement pace and amount (activity counts and steps), length in activity engagement (bout length), accumulation patterns of activity, and movement variability significantly improved the prediction of MMD beyond that found with common covariates (age, diseases, anthropometry, etc). This study identified a subset of actigraphy features collected in free-living conditions that are moderately accurate in identifying persons with clinically-assessed mobility impaired and significantly improve the prediction of MMD. These findings suggest that the combination of features as opposed to a specific feature is important to consider when choosing features and/or combinations of features for prediction of mobility phenotypes in older adults.
Citation Key Alias: lens.org/144-715-377-748-547 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Accelerometers; Actigraphy; Analysis process; Artificial intelligence; Data mining; Disability; Feature extraction; Forecasting; Free livings; General model; Learning systems; Living conditions; Mean square error; Older adults; Patient monitoring; Physical activity; Sedentary; Walking aids; Walking speed; aging; data mining; dept.hms; disability; machine learning; physical activity; sedentary; ⚠️ Invalid DOI

Current activities centered on healthy living and recommendations for the future: A position statement from the HL-PIVOT network - Arena, Ross; Myers, Jonathan; Kaminsky, Leonard A.; Williams, Mark A.; Sabbahi, Ahmad; Popovic, Dejana; Axtell, Robert S.; Faghy, Mark A.; Hills, Andrew P.; Olivares, Silvia Lizett Olivares; Lopez, Mildred; Pronk, Nicolaas P.; et al. (Current Problems in Cardiology, 2021)
We continue to increase our cognizance and recognition of the importance of healthy living (HL) behaviors and HL medicine (HLM) to prevent and treat chronic disease. The continually unfolding events precipitated by the coronavirus disease 2019 (COVID-19) pandemic have further highlighted the importance of HL behaviors, as indicated by the characteristics of those who have been hospitalized and died from this viral infection. There has already been recognition that leading a healthy lifestyle, prior to the COVID-19 pandemic, may have a substantial protective effect in those who become infected with the virus. Now more than ever, HL behaviors and HLM are essential and must be promoted with a renewed vigor across the globe. In response to the rapidly evolving world since the beginning of the COVID-19 pandemic, and the clear need to change lifestyle behaviors to promote human resilience and quality of life, the HL for Pandemic Event Protection (HL-PIVOT) network was established. The 4 major areas of focus for the network are: (1) knowledge discovery and dissemination; (2) education; (3) policy; (4) implementation. This HL-PIVOT network position statement provides a current synopsis of the major focus areas of the network, including leading research in the field of HL behaviors and HLM, examples of best practices in education, policy, and implementation, and recommendations for the future. © 2021 Elsevier Inc.
10 citations (Crossref) [2023-10-31] Type: Review tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85103372602
Keywords: Biomedical Research; COVID-19; Cardiorespiratory Fitness; Chronic Disease; Diabetes Mellitus; Diet; Exercise; Health Education; Health Policy; Healthy; Healthy Lifestyle; Humans; Implementation Science; Information Dissemination; Obesity; Patient Education as Topic; Quality of Life; Review; Risk Reduction Behavior; SARS-CoV-2; Sedentary Behavior; Smoking Cessation; Type 2; body mass; cardiorespiratory fitness; chronic disease; coronavirus disease 2019; dept.hms; education; epidemiology; exercise; health; health behavior; health care personnel; health care planning; health care policy; health education; health promotion; healthy diet; healthy lifestyle; healthy living medicine; human; information dissemination; knowledge; knowledge discovery; law; lifestyle; medical research; medicine; non insulin dependent diabetes mellitus; nutrition; obesity; pandemic; patient education; peer-reviewed; physical activity; psychological resilience; quality of life; risk reduction; sedentary lifestyle; sleep; smoking cessation; syndemic; unhealthy lifestyle behavior